Transnational drug trafficking in Southeast Asia: identifying national limitations to look for regional changes = Tráfico transnacional de drogas en el Sudeste Asiático : identificando las limitaciones nacionales para buscar cambios regionales = Tráfico transnacional de drogas no Sudeste Asiático : identificação de restrições nacionais à procura de mudanças regionais - Luong, Hai Thanh (Revista Criminalidad, 2022)
Over its fifty years of established existence beginning in 1967, the Association of Southeast Asian Nations (ASEAN) has expounded its consolidated and integrated model in political relations, economic developments, and cultural values. However, confronted by threats to global security, ASEAN has also faced the complex impacts of transnational narcotics trafficking (TransNT). The study uses grey literature as secondary data to illustrate the current situations of TransNT in Southeast Asia by way of examining drug trafficking starting from the original countries (Myanmar) through the transit points (Vietnam) to final destination countries (Malaysia). Besides reviewing more than four decades of collaboration, the paper analyses ASEAN’s milestones in building its cooperative mechanism and assesses its institutional framework for combatting TransNT with specific initiatives. The study notes the main barriers and practical challenges that constrain the process of regional cooperation. Some brief recommendations are also suggested for further research in the near future to enhance regional cooperation in combatting transnational crimes.